Geographies of street art: Shepard Fairey and the trans-scalar imagination. (1st September 2014) - Long, Mark
Street art is an emerging art form that insists on unmediated access to the urban realm. It seeks to reconnect urban populations with their surroundings by unsettling apparently banal landscapes that serve to reinforce dominant world-views. It operates through our reimagining of the urban environment, with designs on broader rethinking of our ways-of-being. This article charts new geographic imaginings through Shepard Fairey's 'Power & Glory' exhibition in Charleston, South Carolina. 'Power & Glory' posits a trans-scalar geographical imagination, originating in new senses-of-belonging in the city to describe an arc from local to global; to return, finally, to the city as the immediate scale of existence.